2D Simulation of Two-Phase Flow for Water Jet Cutting Processes with OpenFOAM (2021)
Cold cutting processes are characterized to perform the kinetic energy needed to cut hard materials with little mechanical effort by means of the ultra-high flow pressure pumps, which produce water jets with a flow pressure value of around 90 ksi. These manufacturing processes may be studied considering the fluid mechanics' principles that describe the transport phenomena for inviscid, continuous, and incompressible laminar flows in order to obtain theoretical results approximated to the process conditions. In this sense, the numerical modeling techniques applied in the analysis of water jet cutting processes define an efficient solution of the processes due to the physical analysis of the partial differential equations, which quantify the abrasive flow particles into the system. Taking into account the above, this research proposes a numerical analysis of the physical phenomena through the two-phase flow simulation in steady state with OpenFOAM. Abrasive and liquid phases are quantified to study the turbulent values, which describe the water jet behavior under different working conditions. A 2D model has been computed and discretized, considering the nozzle features in order to visualize and predict the abrasive mixture and flow rejected by using a low computational effort. Therefore, this numerical approach has been validated with a mesh independency analysis developed to verify the relation between the numerical data and the finite number of nodes computed in order to discretize a computational domain and to solve analytically the system proposed until reaching a high approximation between the model and the experimental values obtained during the cutting process by means of abrasive flows.